If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 7 = 16 Reorder the terms: 7 + 3y = 16 Solving 7 + 3y = 16 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3y = 16 + -7 Combine like terms: 7 + -7 = 0 0 + 3y = 16 + -7 3y = 16 + -7 Combine like terms: 16 + -7 = 9 3y = 9 Divide each side by '3'. y = 3 Simplifying y = 3
| (2-4j)x+9+(1+4j)=0 | | -3n-2+6n=7n+26 | | 2.97=x+1.6 | | r+.07r=506 | | -3(2y+4)= | | -25x^2+1=0 | | y-4.7=12.52 | | (6c-7d)-(3c+6cd)= | | 2p^2=-4p+1 | | -4x+2=-6 | | 42x-12x^2=0 | | 5x+11=2(4x+7) | | 3s-(0.5s+7.2)=32.8 | | 40y-40=-40+40 | | M=j-k | | -7-(-3-2g)-10=0 | | 7-5x=27 | | b^4=48 | | 4x+4(x+9)=20 | | y^2-10y+2x+25=0 | | (5a^3+6a)+(-3a^2-5a)= | | 2m-14=6 | | 5(3x+7)-(4x-6)=12 | | 5k-13=2k+2 | | (4+3x+x^2)+(6-9x+x^2)= | | 4t+9=-9t-13 | | -3(1+w)+4w=8 | | -6x+36=28 | | 8-(2x-6)=22 | | 4+8y+9n-2y-2n-17= | | -p^2+8p+4= | | 4z+3(z+7)=-14 |